Implementation of the Waste Bank Application in Realizing the Economic Escalation of the Karangsari Village Community, Lumajang - Ermawati, Emmy; Anisa, Meydia Dwi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Karangsari City is one of the cities in Sukodono District, Lumajang Regency, East Java Region. In this city, the population is generally Javanese and works as livestock breeders. Where there are public offices, especially: Welfare, Training, Housing, Banking, Workplaces, Social Dining Places, and Love Places. Waste banks are a container that can overcome problems faced by local areas through a program to utilize dry waste to be arranged and have managers like banks but what is stored is waste. There are many ways that waste bank supervisors in Karangsari City do to change the natural cultivation behavior of the local community. The purpose of this study is to determine the general picture of the efforts made by waste bank managers, including: knowing the implementation, obstacles, and efforts made to overcome obstacles in implementing the application of waste banks in realizing monetary acceleration for the people of Karangsari City, Lumajang. This movement aims to cultivate the mental, sense and social capacity of the local community in living green, perfect and healthy, especially through sterilization of waste management and involving the local community to have the choice to freely follow, then develop welfare and prevent the occurrence of diseases due to poor conditions that are more widespread locally. , families and people: especially those who are busy handling waste. The results of the training carried out in utilizing waste can produce various forms, plastic waste can make light decorations from used plastic jugs and spoons, hijab holders from used water glasses and raffia rope. For the time being, paper, metal and glass waste can be exchanged, glass waste such as soy sauce containers and glasses that can be used as blooming jars, metal waste such as aluminum jars from leftover food and drinks can be reused as window boxes.